Principles and practice of weight and strength training - Weller, Greg (Crowood Press, 2013)
The practical application of exercise theory by strength and conditioning coaches the world over has helped develop exercise research knowledge into effective training methods. Principles and Practice of Weight and Strength Training will cover how to properly prepare yourself for your chosen sport or activity by increasing strength